Pemanfaatan Augmented Reality pada Media Pembelajaran Interaktif Peredaran Planet - Riyanto Riyanto; Singgih S.R (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2015)
Advancement of technology can be applied in education as a means of teaching whether in formal education institutions or non-formal education. A learning method can be presented using props learning or often known as learning media. Augmented reality as a medium used in visualizing an object that can facilitate in conveying information. AR can be used in a wide range of needs, one of which is the use of the learning media revolution of planets in outer space. The purpose of the research is expected to model augmented reality on planet learning media circulation. The method used in this study using the Multimedia Development Life Cycle (MDLC). MDLC consists of six phases Concept, Design, Material Collecting, Assembly, Testing, and Distribuiton. Application of research results is a learning planet revolution in outer space with AR